2015
DOI: 10.1111/jnu.12126
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies Used by Hospitalized Children With Cancer Undergoing Chemotherapy

Abstract: By gaining knowledge and further understanding about valid coping strategies during chemotherapy treatment, health professionals can mobilize personal and material resources from the children, health teams, and institutions aiming to potentiate the use of these strategies to make treatments the least traumatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 27 publications
1
68
0
15
Order By: Relevance
“…The papers that elicited pediatric cancer patient perspective on their own spiritual care needs were primarily timed during the survivorship timeframe, as patients retrospectively described spirituality in the setting of survivorship . Child voice was included in the following formats: an open‐ended interview on hope, spiritual quality‐of‐life interviews, needs assessment discrete choice exercise, interview responses about coping strategies during chemotherapy hospitalizations or transplant, in association with advance care planning experience, and in integrative therapy use …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers that elicited pediatric cancer patient perspective on their own spiritual care needs were primarily timed during the survivorship timeframe, as patients retrospectively described spirituality in the setting of survivorship . Child voice was included in the following formats: an open‐ended interview on hope, spiritual quality‐of‐life interviews, needs assessment discrete choice exercise, interview responses about coping strategies during chemotherapy hospitalizations or transplant, in association with advance care planning experience, and in integrative therapy use …”
Section: Resultsmentioning
confidence: 99%
“…Adolescents in a study noted that chaplain inclusion was supportive and helpful in translating beliefs and concerns to the oncology care team . Children indicated that their religion, particularly the role of ritual and prayer, helped them cope with treatment. Children perceived religious practices as helpful and a form of support, primarily in strengthening their hope for a cure in a study and fostering relationality in another study .…”
Section: Resultsmentioning
confidence: 99%
“…Nesse contexto, estudos nacionais e internacionais vêm sendo desenvolvidos visando investigar as estratégias de enfrentamento de crianças em eventos estressores, dentre eles situações de abrigamento (Batista, Silva e Reppold, 2010); processo de migração (Caqueo-Urízar et al, 2014); e contextos de saúde, como a situação pré-cirúrgica (Carnier, Padovani, Perosa e Rodrigues, 2015), e a vivência da hospitalização , dos procedimentos médicos invasivos para tratamento oncológico (Motta e Enumo, 2010) e da quimioterapia (Sposito et al, 2015) (Folkman et al, 1986) e avaliaram sua adequabilidade à população-alvo.…”
Section: Desenho E Procedimentosunclassified
“…Coping strategies are learned and evolve from the interaction of cognitive, emotional and behavioural systems [8]. It was found that children undergoing chemotherapy used a variety of coping strategies to deal with the pain and treatment side effects (e.g., understanding the need for chemotherapy, seeking pleasure in nourishment; engaging in entertaining activities and having fun, keeping the hope of cure alive, and finding support in religion) [32]. Studies investigating coping strategies in patients diagnosed with breast cancer found the most used coping strategies were positive self-statements (e.g., "I can handle this pain.…”
Section: Emotional Factorsmentioning
confidence: 99%